PROMOTIONAL STRATEGY THROUGH THE ORGANIZATION OF RELIGIOUS ACTIVITIES AT SDN 10 PENUGAL, PENUKAL ABAB LEMATANG ILIR REGENCY - Edi Zalharis; Saipul Annur; Arwan Arwan; Yuniar Yuniar (LP2M IAI Al-Khairat Pamekasan, 2026)
Increasingly fierce competition between educational institutions requires schools to design effective promotional strategies in building a positive image and strengthening public trust. One of the approaches that is developing is promotion through the organization of religious activities, which not only serves as a means of publication, but also as a medium for strengthening religious and social values. This study aims to examine the school promotion strategy through event organizing religious activities, analyze its impact on the image of the school and public belief, and identify the supporting and inhibiting factors of its implementation. This study uses a qualitative approach with a descriptive method. Data was collected through in-depth interviews, observations, and documentation involving school principals, teachers, activity committees, and related parties. Data analysis is carried out through the stages of data reduction, data presentation, and drawing conclusions. The results of the study show that promotion through religious activities is carried out through systematic planning, community involvement, and the use of social media, thereby forming a religious, active, and value-oriented school image and increasing public trust.